2018
DOI: 10.3390/app8030461
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Studies on Surface Initiated Rolling Contact Fatigue of Turnout Rails by Three-Level Unreplicated Saturated Factorial Design

Abstract: Surface initiated rolling contact fatigue (RCF), mainly characterized by cracks and material stripping, is a common type of damage to turnout rails, which can not only shorten service life of turnout but also lead to poor running safety of vehicle. The rail surface initiated RCF of turnouts is caused by a long-term accumulation, the size and distribution of which are related to the dynamic parameters of the complicated vehicle-turnout system. In order to simulate the accumulation of rail damage, some random sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Crossing wear prediction [18,21,22]. Switch surface RCF prediction [12,20,22,25,26]. Crossing surface RCF prediction [22].…”
Section: Limitations Research Interest Single-layer Co-running Trackmentioning
confidence: 99%
“…Crossing wear prediction [18,21,22]. Switch surface RCF prediction [12,20,22,25,26]. Crossing surface RCF prediction [22].…”
Section: Limitations Research Interest Single-layer Co-running Trackmentioning
confidence: 99%
“…Ma et al [62] presented parameter studies on the surface-initiated rolling contact fatigue (RCF) of turnout rails using a three-level unreplicated saturated factorial design. The results showed that the rail surface-initiated RCF is mainly caused by tangential stress that is high under small creep conditions, normal and tangential stresses that are high under large creep conditions, and normal stress that is high under pure spin creep conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Random variation in vehicle speed and axle load and wheel–rail friction coefficient is considered as normally distributed. 17 Vehicle speed (km/h) is normally distributed as (250, 25 2 ), vehicle axle load (t) is normally distributed as (14, 3 2 ), and the wheel–rail friction coefficient is normally distributed as (0.3, 0.05 2 ). The average number of the vehicles running on the Chinese high-speed railway lines per day (80) was selected as the sample size.…”
Section: Prediction Of Rail Surface-initiated Rcf In the Railway Turnmentioning
confidence: 99%